SELF-HELP PRACTICES: LITERATURE REVIEW - Paičs, Indulis; Mārtinsone, Kristīne; Ļubenko, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In recent years, the number of studies covering mindfulness, self-compassion practices, progressive relaxation, meditation and other self-help therapies or therapeutic interventions has grown rapidly. The vast interest in the field has caused fragmentation in methodological approaches and theoretical models, as well as a diffuse use of terminology, which makes it challenging to compare and critically evaluate the results of various studies. The purpose of this article is to collect and analyze the main trends and conclusions of theoretical and practical research devoted to self-help practices in recent years (2012-2017). The strategy in source selection was the following: a) researching the PsychArticles section of ProQuest database; b) main search criterion: Subject ("Self-Help Techniques"); c) additional search criteria: time of publication; peer-reviewed articles. For further analysis a research question was raised: what research topics appear in these sources and how are they elaborated? To answer it a narrative content analysis approach was used. As a result, five most significant research topics, which show an overview of latest tendencies in the research of self-help practices, were identified.